2018
DOI: 10.34172/ajcmi.2018.18
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of SHV, TEM, CTX-M and OXA-48 β-Lactamase Genes in Clinical Isolates of Pseudomonas aeruginosa in Bandar-Abbas, Iran

Abstract: Background Pseudomonas aeruginosa is an aerobic gram-negative bacillus that is the cause of a range of opportunistic infections in humans. P. aeruginosa is one of the most important pathogenic bacteria in the development of nosocomial infections such as pneumonia associated with intensive care unit (ICU) ventilator, bacteremia, urinary tract infections, and infection in people with severe and septic burns (1, 2). Infections caused by P. aeruginosa are often severe and lifethreatening. P. aeruginosa infection i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 16 publications
(5 reference statements)
0
6
1
Order By: Relevance
“…Several researchers have reported on the concurrence of different β-lactamase genes found in the same strains 38 , 39 . The most common ESBL combination in this study was a combination of bla TEM + bla SHV (40.5%) contrary to Chen et al 31 , who reported the commonest to be bla SHV + bla CTX-M .…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have reported on the concurrence of different β-lactamase genes found in the same strains 38 , 39 . The most common ESBL combination in this study was a combination of bla TEM + bla SHV (40.5%) contrary to Chen et al 31 , who reported the commonest to be bla SHV + bla CTX-M .…”
Section: Discussionmentioning
confidence: 99%
“…In another Iranian survey, Bahrami et al [47] described that blaCTX-M, blaSHV, blaTEM, and blaOXA were the most frequent antibiotic resistance genes detected in 23.95%, 23.08%, 57.29%, and 12.5% of P. aeruginosa strains, respectively. A survey on camel meat [48] showed that the total distribution of ESBL-producing P. aeruginosa was 45%, and blaCTX-M (38.00%), blaSHV (33.30%), and blaTEM (28.50%) were the most commonly detected antibiotic resistance genes. Extended-spectrum b-lactamases are encoded by bla plasmid-mediated genes, particularly blaCTX-M, blaSHV, blaTEM, blaVEB, and blaOXA, which have extended the substratum specificity toward cefotaxime, ceftazidime, and ceftriaxone [49].…”
Section: Discussionmentioning
confidence: 99%
“…Carbapenems are characterized by the distinctive carbapenem structure (see red structure in Figure 1 ) that comprises the β-lactam ring. This unique combination in their molecular structure makes this group of antibiotics exceptionally stable when confronted by β-lactamases [ 36 ], mediated by either the TEM, SHV, CTX, or OXA genes [ 37 ]. Due to the steric hindrance conferred by the 6-α-1R-hydroxyethyl moiety (see blue structure in Figure 1 ) at the β-lactamase binding site [ 38 , 39 ], carbapenems are significantly more stable and more effective than other β-lactams such as penicillin and cephalosporins [ 40 , 41 ].…”
Section: Carbapenemsmentioning
confidence: 99%